Early Medical Technology in Reducing The Mortality Rate in Toll Road Accidents - Reza Aditya Digambiro; Rully Indrawan; Siti Maemunah; Tjuk Sukardimand (Dinasti Publisher, 2024)
Purpose: The research aims to know whether the technological system is effective in bringing improvement to early medical response toward traffic accidents on toll roads in Indonesia, particularly in an attempt to bring down the mortality rate caused by traffic accidents on toll roads. Methods: The current study holds a research design of a mixed-methods approach that mainly adopts the use of qualitative and quantitative measures of structural equation modeling (SEM. Data collected involved survey, interviews, and field observations that focused on perception of accident risk on toll roads and the effect of technology on early medical handling. Result: The findings have therefore confirmed that the traffic accident risk perception on the toll roads is generally perceived low, with a mean perception score averaging at 2.65. On the other side, a positive picture is painted regarding the role of technology in improving timeliness and effectiveness of medical responses: its contribution to early medical handling (3.06) and the impact it can have on the reduction in rates of deaths (2.96). Conclusion: The findings highlight the urgent need for increased public awareness and the development of technology-based emergency strategies. Targeted technological interventions, particularly those enhancing early medical response, could significantly reduce toll road accident fatalities.